Immunogenicity of Vibrio cholerae O1 toxin-coregulated pili in experimental and clinical cholera. - Hall, R H (1991)
A functional tcpA gene, encoding the major subunit of toxin-coregulated pili (TCP), is necessary for Vibrio cholerae O1 Ogawa strain 395 to colonize the human intestine and confer protective immunity to virulent challenge. The immunogenicity of TCP and other antigens in experimental and naturally acquired cholera was determined. Seroconversion to cholera toxin (CT), whole cell preparations, and to Ogawa lipopolysaccharide but not to purified native TCP or to a TcpA mimiotope was found in volunteers. Local intestinal secretory immunoglobulin A from volunteers showed conversions to cholera toxin and lipopolysaccharide but not to TCP. Cholera patients in Indonesia showed a seroconversion rate to TCP of 3 of 6 and a seroconversion to a TcpA mimiotope of 1 of 6. Volunteer and patient sera showed similar vibriocidal seroconversions when assayed against either TCP-positive and TCP-negative V. cholerae O1 strains, suggesting that TCP do not contribute demonstrably to the vibriocidal antigen. We conclude that although seroconversion to TCP can occur in naturally acquired cholera, solid long-term protection can be engendered in the absence of a detectable anti-TCP immune response.